2017
DOI: 10.1167/iovs.16-20607
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Field En Face Swept-Source Optical Coherence Tomography Features of Extrafoveal Retinoschisis in Highly Myopic Eyes

Abstract: Wide-field SS-OCT reveals the spatial distribution of retinoschisis outside the fovea, and associations with retinal vessels and other retinal landmark structures. Further observations on the longitudinal changes and functional damage would help lead to a better understanding of its mechanism and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…[2] In this article, we reported two cases of high myopia with retinoschisis near the vascular arcade with abnormal blood vessels, which have rarely been reported previously. Similar to previously reported cases, [4,5] the location of the abnormal blood vessels was around the arcade rather than the macular area. The nature of this vessel abnormality is still unclear.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[2] In this article, we reported two cases of high myopia with retinoschisis near the vascular arcade with abnormal blood vessels, which have rarely been reported previously. Similar to previously reported cases, [4,5] the location of the abnormal blood vessels was around the arcade rather than the macular area. The nature of this vessel abnormality is still unclear.…”
Section: Discussionsupporting
confidence: 88%
“…[4] According to the location of the retinoschisis, it can be divided into foveal retinoschisis (myopic macular retinoschisis) and retinoschisis away from the fovea, with paravascular retinoschisis being the main form of retinoschisis away from the fovea. [5] Previous literature has shown that paravascular retinoschisis might be a precursor to myopic macular retinoschisis. [6,7] Its mechanism is not well understood, but most authors believe that the combination of vitreoretinal traction, posterior scleral staphyloma, and retinal degeneration in the posterior pole contributes to the development and progression of retinoschisis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in the study of Ruão et al [23], who found extrafoveal retinoschisis in 23.9% of their patients' eyes. However, Xiao et al reported that the most prevalent type of extrafoveal retinoschisis in their sample was the inner type [43], although they selected a sample of patients with a previous diagnosis of extrafoveal retinoschisis, which may explain the difference.…”
Section: Discussionmentioning
confidence: 97%
“…The development of OCT allows better visualization of detailed alterations and early insights of MTM, which can help not only the classification and definition of the disease, but also the assessment of the natural course [ 85 ]. Using widefield SS-OCT, researchers found that coexisting extrafoveal retinoschisis were frequently identified in the inferotemporal area and were related to retinal vessel, microfolds, microbreaks, and staphyloma [ 86 ]. Recently, a new classification system of MTM based on OCT images has been proposed: the retinal stages 1–4 are presented along the vertical axis emphasizing the evolution in the layers perpendicular to the retinal plane; the foveal stages a–c are presented along the horizontal axis emphasizing the evolution in the layers tangential to the retinal plane; the occurrence of an outer lamellar macular hole or epiretinal abnormalities is recorded as “O” or “+” [ 85 ].…”
Section: Oct and Octa For The Assessment Of Pathology In High Myopesmentioning
confidence: 99%